Consumer Eating Behavior and Opinions about the Food Safety of Street Food in Poland - Wiatrowski, Michał (Nutrients, 2021)
Street food plays an increasingly important role in the nutrition of the inhabitants of European cities. Our study aimed to analyze Polish consumers’ attitudes toward food offered in street food outlets, consumers’ eating out behavior, and the factors that determine their choice of meals from street food vendors. A survey was conducted of 1300 adult respondents who eat street food in Poland. The research enabled a detailed and comprehensive assessment of consumer behavior toward the use of street food outlets, as well as consumer opinions on vendors’ functioning, including hygiene and meals offered. Factors determining the frequency of street food consumption, preferred food types, and factors influencing the use of such outlets were identified. The most important factors were the quality of services and meals, personal preferences and price. Using cluster analysis, consumer profiles based on the types of street food outlets and food preferred were identified. Four main street food consumer preference profiles were identified: ‘burger-enthusiasts’, ‘kebab-enthusiasts’ and ‘ice-cream enthusiasts’, and ‘no specific-oriented consumers’. The Internet and social media were identified as information and promotion channels for this form of gastronomy. Results also revealed Polish consumer behavior and opinions about the food safety of street food in Poland. In summary, in Poland the habits of eating typical Polish homemade dishes is being replaced by eating meals in street food outlets, which can be classified as fast food. Increasing consumer knowledge and awareness of the quality and safety of street food may counteract improper hygiene practices of sellers.